2019
DOI: 10.1155/2019/2956920
|View full text |Cite|
|
Sign up to set email alerts
|

Yokukansan Alleviates Cancer Pain by Suppressing Matrix Metalloproteinase-9 in a Mouse Bone Metastasis Model

Abstract: Bone cancer pain control is difficult because it includes various characteristics of pain such as nociceptic and neuropathic pain. In this study, we investigated the effect of yokukansan (YKS), one of the traditional Japanese herbal medicines, on cancer pain in mouse bone metastasis model. Oral administration of YKS significantly alleviated pain behavior measured by quantitative body weight bearing. Furthermore, the pain behavior was also significantly alleviated by intrathecal and intraperitoneal administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Recent studies of YKS for neuropathic pain confirm that YKS relieves mechanical allodynia in partial sciatic nerve ligation mice by regulating the expression of interleukin-6 in astrocytes and/or microglia in the spinal cord [ 24 ] and that YKS has anti-allodynic effects in rats with chronic contraction injuries, which are associated with the blockade of glutamatergic neurotransmission via the activation of glutamate transporters in the spinal cord [ 25 ]. Nakao et al have shown that YKS alleviates cancer pain via suppressing matrix metalloproteinase-9 expression in the bone metastasis model in mice [ 35 ]. The present data show for the first time that YKS affects PTX-induced peripheral neuropathy instead of physical peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of YKS for neuropathic pain confirm that YKS relieves mechanical allodynia in partial sciatic nerve ligation mice by regulating the expression of interleukin-6 in astrocytes and/or microglia in the spinal cord [ 24 ] and that YKS has anti-allodynic effects in rats with chronic contraction injuries, which are associated with the blockade of glutamatergic neurotransmission via the activation of glutamate transporters in the spinal cord [ 25 ]. Nakao et al have shown that YKS alleviates cancer pain via suppressing matrix metalloproteinase-9 expression in the bone metastasis model in mice [ 35 ]. The present data show for the first time that YKS affects PTX-induced peripheral neuropathy instead of physical peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show that YKS is clinically effective against various chronic pain diseases [ 19 , 46 ], and some basic studies have been reported on its mechanisms of action [ 20 , 21 , 47 ]. The activation of N-methyl- d -aspartic acid (NMDA) receptor, a glutamate receptor, is considered a central sensitization [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports that the behavioral and psychological symptoms in patients with dementia improved due to YKS use [ 7 , 17 , 18 ]. Recent clinical investigations and preclinical basic studies indicated that YSK could have an analgesic effect on neuropathic pain [ 19 , 20 , 21 ]. However, only a few reports have verified the analgesic effect of YKS on acute pain, and the analgesic effect of combined treatments with other traditional medicines have rarely been verified.…”
Section: Introductionmentioning
confidence: 99%
“…The analgesic effect of YKS has been proven in some animal models, including a chronic constriction injury (CCI) model ( Suzuki et al, 2012 ; Suga et al, 2015 ), partial sciatic nerve ligation (PSL) model ( Ebisawa et al, 2015 ), bone metastasis model ( Nakao et al, 2019 ), and adjuvant arthritis model ( Honda et al, 2013 ). Several factors are involved in the complex development and promotion of neuropathic pain.…”
Section: Action Mechanisms Of Yokukansan For Neuropathic Painmentioning
confidence: 99%